Morphoquantitative aspects of nitrergic myoenteric neurons from the stomach of diabetic rats supplemented with acetyl-L-carnitine - Fregonesi, CEPT; Molinari, S. L.; Alves, AMP; Defani, M. A.; Zanoni, J. N.; Bazotte, R. B.; Neto, MHD (Blackwell Verlag Gmbh, 2005)
The NADPH-diaphorase (NADPH-d) positive myoenteric neurons from the body of the stomach of rats with streptozotocin-induced diabetes with or without supplementation with acetyl-L-carnitine (ALC) were evaluated. At the age of 105 days the animals were divided into four groups: normoglycaemic (C), normoglycaemic supplemented with ALC (CC), diabetic (D) and diabetic supplemented with ALC (DC). The supplementation with ALC (200 mg/kg body weight/day) to groups CC and DC was made during 105 days. After this period the animals were killed and the stomach removed and subjected to the histochemical technique of NADPH-d for the staining of the neurons of the myoenteric plexus. The area of 500 neurons of each group was investigated, as well as the neuronal density in an area of 23.84 mm(2) in each stomach. ALC promoted reduction (P < 0.05) of fasting glycaemia, water ingestion and areas of the profiles of the cell bodies of the NADPH-d neurons in the diabetic animals. The density of these neurons was not statistically different in the groups studied. It is suggested, therefore, a moderate neuroprotective effect of ALC, because the diminishment of the areas of the neuronal profiles in the supplemented diabetic animals, although being statistically significant relative to the non-supplemented diabetics, was not sufficient to equal the values from the non-diabetic controls.